Optimalisasi Penggunaan Media ICT dalam Pembelajaran IPA untuk Meningkatkan Hasil Belajar Siswa Kelas IXc Pada Semester II Tahun 2014/2015 di SMPN 4Kota Solok - Hurriyati Hurriyati (Eduscience Development Journal, 2019)
This research is motivated by the conditions when learning which seems to tend to make students less motivated to learn science. Students sometimes feel scared, lazy and bored because they think that science is difficult, full of formulas and so many concepts must be memorized that students expect the science class to end soon. On the other hand students will be able to involve themselves fully both emotionally and intellectually when seeing a spectacle on the screen. When the author occasionally utilizes ICT media in student learning seems motivated to follow it. The purpose of this study was to achieve the blessing of Allah SWT by trying to optimally improve the quality of learning through the effort "Optimizing the Use of ICT Media in Science Learning to Improve Student Learning Outcomes in Class IXc in Semester II of 2014/2015 at SMPN 4 Solok City". This research was conducted in two cycles. In cycle 1 students are given the opportunity to prepare subject matter and present it using Microsoft Power Point programs. Student learning outcomes have increased compared with the initial conditions, and it appears students have begun to be actively involved in learning. But the authors are still not satisfied with this achievement and see an opportunity that might improve student mastery of the subject matter by providing a pretest and posttest at every 3 hour lesson meeting. Alhamdulillahi Robbil ‘alamin, this research can finally prove that Optimizing the Use of ICT Media in Science Learning is able to Improve Student Learning Outcomes of Class IXc in Semester II of 2014/2015 at SMPN 4 Kota Solok. Therefore, the authors hope that in the future teachers can optimize the use of ICT media in learning by actively involving students because the development of technology is now more controlled by our students so that it will be even more meaningful if we direct their ability to support their mastery of learning.